Global dynamic timelines for IPRs harmonization against software piracy - Antonio R. Andrés; Simplice A. Asongu (Institute for Advanced Development Studies (INESAD), 2013)
This paper employs a recent methodological innovation on intellectual property rights (IPRs) harmonization to project global timelines for common policies against business software piracy. The findings on 99 countries are premised on 15 fundamental characteristics of software piracy based on income-levels (high-income, lower-middle-income, uppermiddle- income and low-income), legal-origins (English common-law, French civil-law, German civil-law and, Scandinavian civil-law) and, regional proximity (South Asia, Europe & Central Asia, East Asia & the Pacific, Middle East & North Africa, Latin America & the Caribbean and, Sub-Saharan Africa). The results broadly show that a feasible horizon for the harmonization of blanket policies ranges from 4 to 10 years.
Keywords: F42; K42; O34; O38; O57; 330; software piracy; intellectual property rights; panel data; convergence